Disseminated tuberculosis and diagnosis delay during the COVID-19 era in a Western European country: a case series analysis - Roure, Sílvia; Vallès, Xavier; Sopena, Nieves; Benítez, Rosa Maria; Reynaga, Esteban A.; Bracke, Carmen; Loste, Cora; Mateu, Lourdes; Antuori, Adrián; Baena, Tania; Portela, Germán; Llussà, Judith; et al. (Frontiers in Public Health, 2023)
Background: Disseminated tuberculosis is frequently associated with delayed diagnosis and a poorer prognosis. Objectives: To describe case series of disseminated TB and diagnosis delay in a low TB burden country during the Covid-19 period. Methodology: We consecutively included all cases of disseminated TB reported from 2019 to 2021. We collected socio-demographic information, clinical, laboratory and radiological findings. Results: We included all 30 cases reported during the study period—5, 9 and 16 in 2019, 2020 and 2021 respectively—20 (66.7%) of whom were male and whose mean age was 41 years. Twenty-five (83.3%) were of non-EU origin. The most frequent system involvement was central nervous system (N=8; 26.7%) followed by visceral (N=7; 23.3%), gastro-intestinal (N=6, 20.0%), musculoskeletal (N=5; 16.7%) and pulmonary (N=4; 13.3%). Hypoalbuminemia and anaemia were highly prevalent (72% and 77%). The median of diagnostic delay was 6.5 months (IQR 1.8–30), which was higher among women (36.0 months; p=0.002). Central nervous system involvement and pulmonary involvement were associated with diagnostic delay among women. We recorded 24 cured cases, 2 deaths, 3 cases with post-treatment sequelae and 1 lost-to-follow up. We observed a clustering effect of cases in low-income neighbourhoods (p<0.001). Conclusions: There was a substantial delay in the diagnosis of disseminated TB in our study region, which might impacted the prognosis with women affected more negatively. Our results suggest that an increase in the occurrence of disseminated TB set in motion by diagnosis delay was a secondary effect of the Covid-19 pandemic on health services.